Palm Oil Mill Effluent Treatment Through Combined Process Adsorption and Membrane Filtration - Muhammad Said; Siti Rozaimakh Sheikh Abdullah; Abdul Wahab Mohammad (Sriwijaya Journal of Environment, 2016)
Abstract: The growth in palm oil production also leads to an Increase in the production of palm oil mill effluent (POME). Nowadays, POME was treated using an open lagoon but this method is ineffectiveness in complying with the standards for water disposal. Therefore, efficient and cohesive treatment system is highly desired to ensure the final discharge of the treated water meets the effluent discharge standards. Initially, the POME was treated through adsorption, followed by UF membranes roomates were intended to reduce COD, TSS and turbidity up to 88%, 99%, and 98%, while the final treatment of RO membranes can reduce BOD, COD and color up to 92%, 98% and 99%. To determine the optimum condition of the RO membrane, response surface methodology (RSM) was used. The results showed there was correlation between all key variables. POME concentration, trans-membrane pressure, pH and time would give significant effects in reducing the parameters in POME treatment with the optimum condition of 15.77% for POME concentration, 3.73 for pH, 0.5 bar trans-membrane pressure and 5 hours for filtration time. To predict COD removal, the results were analyzed by applying the artificial neural network (ANN) to derive a mathematical model.Keywords: POME, Adsorption, Membrane filtration, COD, RSM, ANNAbstrak (Indonesian): Pertumbuhan produksi minyak kelapa sawit juga meningkatkan produksi air buangan minyak kelapa sawit (POME). Sekarang ini, POME diolah menggunakan kolam terbuka tetapi metode ini tidak efisien dan tidak memenuhi persyaratan standar air buangan industri. Oleh karena itu, diperlukan suatu sistem pengolahan yang efektif dan terpadu untuk memastikan air buangan pada tahap akhir telah memenuhi standar air buangan.  Pada awalnya, POME diolah melalui adsorpsi dan diikuti oleh membran UF dengan tujuan untuk mengurangi kadar COD, TSS dan kekeruhan hingga 88%, 99% dan 98%, masing-masing.  Sementara itu, pada proses akhir digunakan membran RO yang berhasil menurunkan kadar BOD, COD dan warna hingga 92%, 98%, dan 99%, masing-masing.  Untuk menentukan kondisi optimum dari membran RO digunakan metode respon permukaan (RSM).  Hasil memperlihatkan ada korelasi antara semua variabel. Konsentrasi POME, tekanan trans membran, pH aturan dan waktu memberikan pengaruh penting dalam pengurangan parameter pada pengolahan POME, dengan kondisi operasi optimum sebagai berikut: 15,77% bagi konsentrasi, 3,73 bagi pH, 0,5 bar bagi tekanan trans membran, dan 5 jam waktu filtrasi.  Untuk memprediksi penghilangan COD, hasil diperiksa menggunakan metode jaringan saraf tiruan (ANN). Hal ini bertujuan untuk mendapatkan suatu model matematika.Kata kunci: POME, Adsorpsi, Membran filtrasi, COD, RSM, ANN